Protein folding as a driving force for dual protein targeting in eukaryotes - Kalderon, Bella; Pines, Ophry (Frontiers in Molecular Biosciences, 2014)
It is well documented that in eukaryotic cells molecules of one protein can be located in several subcellular locations, a phenomenon termed dual targeting, dual localization, or dual distribution. The differently localized identical or nearly identical proteins are termed “echoforms.” Our conventional definition of dual targeted proteins refers to situations in which one of the echoforms is translocated through/into a membrane. Thus, dual targeted proteins are recognized by at least one organelle's receptors and translocation machineries within the lipid bilayer. In this review we attempt to evaluate mechanisms and situations in which protein folding is the major determinant of dual targeting and of the relative distribution levels of echoforms in the subcellular compartments of the eukaryotic cell. We show that the decisive folding step can occur prior, during or after translocation through the bilayer of a biological membrane. This phenomenon involves folding catalysts in the cell such as chaperones, proteases and modification enzymes, and targeting processes such as signal recognition, translocation through membranes, trapping, retrotranslocation and reverse translocation.